Optical Emission Spectroscopy of CO2 Plasma Produced by CCP-Type Discharge - Saidon, Nur Aqilah; Mohamed Ali, Riyaz Ahmad; Nayan, Nafarizal; Hamed, Noor Kamalia; Azman, Zulkifli; Natasya Salsabiila; Asri, Herman (International Journal of Integrated Engineering, 2026)
This study investigates the decomposition of carbon dioxide (CO2) using capacitively coupled plasma (CCP) technology. CO2, a primary greenhouse gas, is decomposed into valuable products like carbon monoxide (CO) through plasma technology, a promising possibility for CO2 reduction due to its efficiency and low energy consumption. The experiment systematically examines the decomposition of  CO2 and its interaction with Argon. In-situ optical emission spectroscopy (OES) monitors the reaction while plasma temperature is assessed to understand the decomposition behavior of CO2. Varying ratios of Ar are introduced into the plasma to explore their effects on CO₂ decomposition. The effects of discharge power and different working pressures on CO2 decomposition were analyzed to provide insights into the process within CCP plasma. The results indicate that the introduction of a small amount of Ar, which is 20% of Ar and 80% of CO2, shows that adding a small amount of Ar enhances CO2 dissociation by 10%. A discharge power of 500W was identified as the most effective discharge power to dissociate the CO2, and the working pressure of 200mTorr produced the most stable plasma discharge compared with other working pressures. Electron temperature (Te) confirmed the impact of gas composition on plasma characteristics, as Te increased steadily and allowing electrons to gain more energy sustained a higher temperature to dissociate CO2. Hence, these findings contributed to the optimization of CO2 conversion processes using non-thermal plasma technology for reducing greenhouse gas emissions.